Liquidity Management and the Performance of Commercial Banks in Nigeria - Jibrin Suleiman Hassan; Oyedele Oloruntoba (International Journal on Economics, Finance and Sustainable Development, 2022)
The study focused on liquidity management and its effect on the performance of commercial banks in Nigeria. The study adopted correlational research design. The scope of the study was between 2008 to 2018, a period of 10 years. The study data were collected from the annual report of CBN and NDIC. The data were analysed with the aid of OLS. The study used Non-performing loan ratio, cash reserve requirement, Loan to deposit ratio and liquidity ratio as the components of liquidity management while financial performance was measured as return on equity of Nigerian commercial banks. The study revealed that cash reserve requirement, loan to deposit ratio and liquidity positively and significantly impact the financial performance in Nigerian commercial banks while non-performing loan ratio exhibits a negative but significant relationship with the performance of strategies to reduce non-performing loans. In addition, the managers should revise the loan approval process of their banks so as to reduce the level of nonperforming loans in their banks. Also, that Central Bank of Nigeria which is the nation’s apex bank should supervise and formulate policies that will encourage banks to improve on their international functions.